'Are you being served?' The Jewish Agency and the absorption of Ethiopian immigration. Issue 2 (2nd April 2016) - Binhas, Adi
Abstract: This article addresses the question of how the Israeli government and the Jewish Agency for Israel (JAFI) handled the absorption of Ethiopian immigrants in the early 1990s. It shows that, reflecting the historic rivalry between the two organizations, their interaction lacked a clear division of roles and was mired by rivalry and conflicting interests. As a result, the individual immigrant, besides dealing with predictable absorption difficulties, had to cope with bureaucratic failures.